Pengaruh Fasilitas Kerja Dan Pengembangan Karir Terhadap Kinerja Karyawan Dengan Kepuasan Kerja Sebagai Variabel Intervening Pada PT.Bakrie Pasaman Plantations - Robby Dharma; Yasmin Eliza; Della Asmaria Putri; Mulyadi, olandari (Journal of Science Education and Management Business, 2022)
Abstract. The purpose of this study was to determine how much influence work facilities and career development have on employee performance with job satisfaction as an intervening variable at PT. Bkrie Pasaman Plantations Air Balam . Methods of data analysis using a questionnaire, with a sample of 82 respondents. The data analysis method used is multiple linear regression analysis. Based on the results of the study indicate that there is a positive and significant influence between work facilities on improving employee performance,Meanwhile, Job Facilities and Career Development through Job Satisfaction have an effect of 69.2% while the remaining 30.8% is influenced by other variables outside of this study. Based on the results of this study, it is expected that the company's management can improve performance by improving work facilities through office equipment, transportation, career development through training, education and job satisfaction through increasing salaries and promotions at PT. Bakrie Pasaman Plantaions Air Balam Pasaman Barat. Keywords: work facilities,career development,employee performance and jon satisfaction